Clostridium innocuum is a vancomycin-resistant pathogen that may cause antibiotic-associated diarrhoea. (November 2018) - Chia, J.-H.; Wu, T.-S.; Wu, T.-L.; Chen, C.-L.; Chuang, C.-H.; Su, L.-H.; Chang, H.-J.; Lu, C.-C.; Kuo, A.-J.; Lai, H.-C.; Chiu, C.-H.
Abstract: Objectives: Clostridium innocuum can cause extraintestinal infection in patients with underlying diseases. The role of C. innocuum in antibiotic-associated diarrhoea (AAD) remains unknown. Methods: Clinical information of 103 patients from whom C. innocuum was isolated was reviewed. We carried out cellular and animal experiments to examine the pathogenic potential of C. innocuum in AAD. Results: Eighty-eight per cent (91/103) of the 103 patients received antibiotics within 2 weeks of diarrhoea onset. Patients were further classified into two groups, severe colitis and diarrhoea, according to clinical severity level. The mortality rate was 13.6% (14/103) among the patients from whom C. innocuum was isolated. The lowest concentrations at which 90% of the isolates were inhibited for metronidazole and vancomycin were 0.5 and 16 mg/L, respectively. All isolates tested were susceptible to metronidazole but resistant to vancomycin. Nineteen randomly selected isolates (ten from severe colitis group, nine from diarrhoea group) were subjected to further in vitro cellular examinations. The level of cytotoxicity to Vero cells was significantly higher in isolates from the severe colitis group at both 24 and 48 hours after inoculation (24 and 48 hours, p 0.042 and 0.033, respectively). We observed apoptotic changes that subsequently led to cell death in C. innocuum –infected Vero cells. Tissue damages, necrotic changes and oedema were observed in the mouse ileal loop infected by C. innocuum. Conclusions: Vancomycin-resistant C. innocuum may play a potential role as a causative agent of AAD. The clinical manifestations of AAD caused by C. innocuum were diarrhoea or severe colitis, including pseudomembranous colitis.